STRUCTURE AND FUNCTION OF THE CARDIOVASCULAR SYSTEM OF THE HUMAN BODY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article describes the structure of each of the cardiovascular system and its operation.